Fiber-optical equipment for technical diagnostics of high-rise architectural structures (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The problem of ensuring reliable perception of design loads by load-bearing building structures after the negative impact of hydrometeorological or destructive operational factors is especially acute with the increase in the number of storeys of architectural structures. This task is necessarily taken into account at the design stage. However, in the calculations it is not possible to take into account the actual state of the load-bearing structure of the building after an earthquake, storm or fire. The modern concept of "operation to a pre-failure state" is based on various methods of forecasting the technical condition, in particular - identification of destruction at the initial stage of their development. The practical use of this concept requires the introduction of new, more effective, easy-to-use, automated means and devices for technical diagnostics and forecasting the technical condition of building elements and structures and significantly complicates monitoring procedures. Trends in the development of modern methods of operation show that it is the use of reliable, verified, insensitive to disturbances diagnostic means and devices that are organically built into the information and measuring system that ensure high operational efficiency and reliability of the functioning of architectural structures. Existing means and devices for diagnosing the technical condition of architectural structures operate under conditions of concentrated influence of destabilizing factors. It is these disturbances that do not allow for effective diagnostics and forecasting of the technical condition of architectural structures that meet modern operational requirements. Analysis of known solutions proves that for modern monitoring of technical condition new means of diagnostics and forecasting are in demand, namely - fiber optic devices insensitive to most operational destabilizing factorsThat is why the scientific task of creating diagnostic tools that function in difficult operating conditions and are adapted for continuous, long-term and reliable monitoring of the condition of architectural structures under the action of concentrated influence of destabilizing factors is relevant and in demand by construction companies, the solution and practical use of which significantly increases the level of safety of super-tall buildings. To overcome a certain restraint in the improvement of measuring equipment, a direction of development of measuring transducers based on the use of optical radiation for recording physical effects has been formed. The use of unique properties of optical materials is an effective solution for the creation of fiber-optic measuring transducers and information and measuring system communication lines. Technological breakthrough in the production of special optical glass has allowed it to largely surpass the properties of known materials.The task is solved by providing a device for determining angular displacements, which contains a unit for recording and processing information, a laser emitter, a photodetector, and which is characterized in that the laser emitter and the compensating interferometer connected to the photodetector are connected to the primary branches of a two-way optical splitter, the secondary branches of which contain optical filters and are connected to planar light guides, which contain fiber Bragg gratings and are fixed along the internal space of the building element parallel to and perpendicular to its planes.
Keywords: supertall building; technical monitoring; fiber optic sensor